Creation of New Cities in Uganda: Social Economic and Political Implications - Mbabazi, Jonas; Atukunda, Phoebe (Advocates Coalition for Development and Environment ACODE, 2020)
Urbanization is a global trend and has largely been a positive force for economic growth, poverty reduction and human development. Urbanization is understood as a population shift from rural to urban areas, it is the gradual increase in the proportion of people living in urban areas and the ways in which each society adapts to the change. It is predominantly the process by which towns and cities are formed and become larger as more people begin living and working in urban areas (GoU, 2017). The National Library of Medicine defines urbanization as” the population shift from rural areas to urban areas, the decrease in the proportion of people living in rural areas, and how each society adapts to this change”2. Urbanization is also looked at as a process by which towns and cities are formed. Cities are important drivers of development and poverty reduction in both urban and rural areas because they are places where entrepreneurship, technological innovation and other economic activity can flourish (United Nations, 2014).